Theoretical framework of the Industry 4.0 risks from sustainability perspective - Soltovski, Ramon; Rodrigues, Thales Volpe; Pontes, Joseane; Resende, Luis Mauricio Martins (Revista Competitividade e Sustentabilidade, 2022)
Industry 4.0 is a topic little discussed today, especially in relation to the possible negative risks generated by it. In this way, this work aims to raise and discuss the risks of the Fourth Industrial Revolution currently found in the literature from a sustainability perspective and develop a theoretical framework to represent them. For this, a methodology of systematic analysis of the literature was used to relate the relevant works to the theme and thus to discuss them. Two databases (Scopus and Web of Science) were used in which 7772 articles were evaluated, of which 66 were used for the discussion. The 28 risks found were grouped into four dimensions (Economic Risks, Social Risks, Environmental Risks, and Technological Risks) where their relationships were studied and represent in the theoretical framework constructed. In this way, in addition to contributing to the academy building more theoretical contribution to the theme, the risks raised can help managers and companies to checkpoints of attention before implanting technologies and concepts of industry 4.0.